APPLICATIONS IN FOREIGN CURRENCY PRIMA CV ELLINDO MONEY CHANGER - Wisnu Sutrisno; Ire Puspa Wardhani, Skom, MMSI (Jurnal Sistem Informasi, 2004)
This explains the scientific writing about the design of application programs forforeign currency transactions by using Visual Basic 6.0 programming language.In scientific writing database is also used by Visual Data Manager (VisData)integrated in Visual Basic 6.0 program itself. Consists of three tables namelyCurrency,Customer and Transaction.In the end application program for foreign currency transactions will be applied to theCV. Prima Ellindo Money Changer for ease in performing activities of transactions,such as creating a memorandum of the transaction and making a report.